Impact of non-hepatic hyperammonemia on mortality in intensive care unit patients: a retrospective cohort study - Jae Heon Kim (The Korean Association of Internal Medicine, 2021)
Background/Aims The effect of hyperammonemia on the mortality in patients with liver cirrhosis is well documented. However, little is known about the impact of hyperammonemia on mortality among intensive care unit patients without hepatic disease. We aimed to investigate factors associated with non-hepatic hyperammonemia among intensive care unit patients and to evaluate the factors related to the 7- and 90-day mortality. Methods Between February 2016 and February 2020, 948 patients without hepatic disease who had 972 episodes of admission to the intensive care unit were retrospectively enrolled and classified as hyperammonemia grades 0 (≤ 80 μg/dL; 585 [60.2%]), 1 (≤ 160 μg/dL; 291 [29.9%]), 2 (≤ 240 μg/dL; 55 [5.7%]), and 3 (> 240 μg/dL; 41 [4.2%]). Factors associated with hyperammonemia and the 7- and 90-day mortality were evaluated by multivariate logistic regression analysis and Cox regression analysis, respectively. Kaplan-Meier survival curves for the 7- and 90-day mortality were constructed. Results The independent risk factors for hyperammonemia were male sex (odds ratio, 1.517), age (0.984/year), acute brain failure (2.467), acute kidney injury (1.437), prothrombin time-international normalized ratio (2.272/unit), and albumin (0.694/g/dL). The 90-day mortality rate in the entire cohort was 24.3% and gradually increased with increasing hyperammonemia grade at admission (17.9%, 28.2%, 43.6%, and 61.0% in patients with grades 0, 1, 2, and 3, respectively). Additionally, non-hepatic hyperammonemia was an independent predictor of the 90-day mortality in intensive care unit patients. Conclusions Non-hepatic hyperammonemia is common (39.8%) and associated with the 90-day mortality among intensive care unit patients.